UTILIZATION OF TRADITIONAL DRUG PLANT BY THE PEOPLE'S COMMUNITY SUBDISTRICT DISTRICT OF KUPANG TIMUR 2016 - JEFRIN SAMBARA; NI NYOMAN YULIANI; MARIA YUNIATI EMERENSIANA (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2016)
The number of medicinal plants in Indonesia varied, until recently the number is not yet known with certainty, so that the necessary documentation thoroughly for the use of plants as raw material treatment. The purpose of this study was to determine the types of plants and herbs used in the treatment, the part used, method of use, efficacy and usage rules by Village community Merdeka Eastern District of Kupang. This type of research is descriptive qualitative. Data obtained from the survey by interviewing respondents. The population in this study were all Village community Merdeka Eastern District of Kupang. The sample in this study is that people who have knowledge of traditional medicine with the use of medicinal plants. The research was conducted in June-July 2016. It was found 39 species of medicinal plants. Types of plants with the stature of trees, shrubs, bushes, and Terna. Parts used by utilizing the bark, leaves, fruits, rhizomes, seeds, sap, and roots. Ways of processing that is boiled, baked, vaporized, crushed, soaked and fried, and served in fresh form. A medicinal herb used in a way tied, taped, drunk, gargled, smeared, worn wash, and wear a shower. The results showed that the criteria behind the choice of plants depends on the knowledge, plant availability and trust each Penyehat Traditional (Hattra). From the results of this study concluded that there are different types of medicinal plants and parts used in processing and the use of different, and there are several criteria behind the choice of medicinal plants.